2022
DOI: 10.1093/plphys/kiac048
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a pyridoxal-phosphate phosphatase rescues Arabidopsis lacking an endoplasmic reticulum ATP carrier

Abstract: The endoplasmic reticulum (ER)-located ATP/ADP-antiporter (ER-ANT1) occurs specifically in vascular plants. Structurally different transporters mediate energy provision to the ER, but the cellular function of ER-ANT1 is still unknown. Arabidopsis (Arabidopsis thaliana) mutants lacking ER-ANT1 (er-ant1 plants) exhibit a photorespiratory phenotype accompanied by high glycine levels and stunted growth, pointing to an inhibition of glycine decarboxylase. To reveal whether it is possible to suppress this marked phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
2
2
Order By: Relevance
“…Although, as nitrate assimilation is reduced under high CO 2 ( Bloom et al 2010 , 2020 ; Bloom 2015 ), this could account for the more drastic phenotype under this condition. This is in contrast to the recently described er-ant1 mutant which suffers a PLP deficiency that impacts photorespiration and is alleviated by growth under high CO 2 ( Altensell et al 2022 ). Thus, the pdx3 phenotype is a consequence of a different metabolic defect.…”
Section: Discussioncontrasting
confidence: 92%
“…Although, as nitrate assimilation is reduced under high CO 2 ( Bloom et al 2010 , 2020 ; Bloom 2015 ), this could account for the more drastic phenotype under this condition. This is in contrast to the recently described er-ant1 mutant which suffers a PLP deficiency that impacts photorespiration and is alleviated by growth under high CO 2 ( Altensell et al 2022 ). Thus, the pdx3 phenotype is a consequence of a different metabolic defect.…”
Section: Discussioncontrasting
confidence: 92%
“…Although, as nitrate assimilation is reduced under high CO 2 (Bloom et al, 2010; Bloom, 2015; Bloom et al, 2020), this could account for the more drastic phenotype under this condition. This is in contrast to the recently described er-ant1 mutant which suffers a PLP deficiency that impacts photorespiration and is alleviated by growth under high CO 2 (Altensell et al, 2022). Thus, the pdx3 phenotype is a consequence of a different metabolic defect.…”
Section: Discussioncontrasting
confidence: 92%
“…In Escherichia coli (Enterobacteriaceae, Escherichia)a protein encoded by the gene YbhA was identified as a PLPP (Sugimoto et al, 2018). In Arabidopsis thaliana (Cruciferae, Arabidopsis), a PLPP protein (AtPLPP1) encoded by At2g33255 was annotated as a member of the HAD‐like superfamily and has 44% similarity to the YOR131C protein sequence, which was identified as a PLPP in Saccharomyces cerevisiae (Saccaromycetes, Saccharomycetaceae) (Altensell et al, 2022; Kuznetsova et al, 2015). In this study, we identified the BmPLPP2 as a PLPP which contains a HAD domain and a phosphatases domain.…”
Section: Discussionmentioning
confidence: 99%